Influence of Effective Pressure on Percolation Rate of Coal - Fukun Xiao; Wenhai Xu; Renhe Li; Fengrui Zhang; Lei Xu; Le Xing; Zhiyuan Hou (Advances in Materials Science and Engineering)
To study the role of the effective pressure on the percolation rate of coal, the effect of gas pressure, gas adsorption, and temperature on coal is taken into consideration comprehensively. Starting from the research direction of effective pressure and porosity, the coal body percolation rate and effective pressure equations considering the influence of temperature and gas pressure are established. The experiments on the percolation characteristics of raw coal are implemented under different effective pressure by using the independently developed thermos-solid-gas linking triaxial servosystem. The theoretical equation of the effective pressure and percolation rate of coal is calculated with the finite element software COMSOL, and the results obtained from the theoretical equation agree well with the experimental results. The results show that the percolation rate of coal gradually decreases with the growth of the effective pressure when the gas pressure and temperature are kept unchanged. Therefore, the results of the research are of certain reference value for the effective prevention of gas disaster.